2009
DOI: 10.1021/om9009069
|View full text |Cite
|
Sign up to set email alerts
|

Iron(0) Tricarbonyl Complexes of Microbially Derived Cyclohexadiene Ligands Containing Quaternary Stereocenters

Abstract: SE 2010, 'Iron(0) tricarbonyl complexes of microbially derived cyclohexadiene ligands containing quaternary stereocenters',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The precursor for complex 1 , diene 2 , could be synthesized via a cycloaddition reaction between an acrylate ester and furan, both available from biorenewable sources (Scheme ). Alternatively, structurally similar dienes can also be made via biocatalytic cis -dihydroxylation of aromatic molecules, and these have been exploited using iron carbonyl chemistry. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…The precursor for complex 1 , diene 2 , could be synthesized via a cycloaddition reaction between an acrylate ester and furan, both available from biorenewable sources (Scheme ). Alternatively, structurally similar dienes can also be made via biocatalytic cis -dihydroxylation of aromatic molecules, and these have been exploited using iron carbonyl chemistry. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…We have recently explored iron diene complexation in the context of ipso-ortho arene dihydrodiol 4 and its derivatives and found that complexation of a tricarbonyliron fragment to methyl ester 7 affords solely the isomer in which the hydroxyls are endo and the ester is exo ( 8 , Scheme 3 ) [ 45 ]. This result is noteworthy, since in contrast to 5 , ligand 7 presents Lewis basic functionality on both sides of the ring.…”
Section: Introductionmentioning
confidence: 99%